2020
DOI: 10.1055/s-0040-1721350
|View full text |Cite
|
Sign up to set email alerts
|

Update on Thrombocytopenia in Pregnancy

Abstract: Thrombocytopenia, defined as platelet count < 150,000 mm3, is frequently diagnosed by obstetricians since this parameter is included in routine surveillance during pregnancy, with an incidence of between 7 and 12%. Therefore, decisions regarding subsequent examination and management are primordial. While most of the cases are due to physiological changes, as gestational thrombocytopenia, other causes can be related to severe conditions that can lead to fetal or maternal death. Differentiating these conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
(209 reference statements)
1
9
0
8
Order By: Relevance
“…On the other hand, pregnant women with severe thrombocytopenia are at a high risk to develop the bleeding disorder during and after delivery due to the normalization of coagulant activity near to the term and following delivery that can be associated with profound maternal and fetal morbidity and mortality. 22,44 Moreover, multivariate logistic regression analysis showed that residence and gestational ages (trimesters) had a statistically significant association with thrombocytopenia. Gestational ages within first trimester (AOR: 0.183, 95% CI, 0.057-0.593, P = 0.001) and gestational ages within second trimester = 0.264, 95% CI, 0.092-0.752, P = 0.009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pregnant women with severe thrombocytopenia are at a high risk to develop the bleeding disorder during and after delivery due to the normalization of coagulant activity near to the term and following delivery that can be associated with profound maternal and fetal morbidity and mortality. 22,44 Moreover, multivariate logistic regression analysis showed that residence and gestational ages (trimesters) had a statistically significant association with thrombocytopenia. Gestational ages within first trimester (AOR: 0.183, 95% CI, 0.057-0.593, P = 0.001) and gestational ages within second trimester = 0.264, 95% CI, 0.092-0.752, P = 0.009).…”
Section: Discussionmentioning
confidence: 99%
“…O enfermeiro é o profissional de saúde que pode ser fundamental na assistência multiprofissional no manejo da Síndrome HELLP e o pré-natal é o momento crucial de escuta e avaliação da paciente. Apesar da enfermagem explorar o conhecimento no contexto da obstetrícia e os seus aspectos, devido à particularidade e alta complexidade dos casos críticos, o profissional deve buscar maior eficiência no monitoramento e gerenciamento dos casos suspeitos ou confirmados de Síndrome HELLP para compreender os mecanismos, sinais e sintomas da sua ocorrência (SUBTIL et al, 2020).…”
Section: Resultsunclassified
“…Risiko dari prosedur regional anestesi pada kasus trombositopenia yaitu meningkatnya risiko spinal atau epidural hematom harus menjadi pertimbangan sebelum keputusan pemilihan prosedur anestesi ditegakkan. 3 Selanjutnya akan dibahas mengenai trombositopenia pada kehamilan dan manajemen anestesi perioperatif pada kehamilan dengan trombositopenia.…”
Section: Pendahuluanunclassified